Antimicotic effect of thymol on strains of Candida albicans: in vitro study - Ayala, J (2019)
Objective: To determine the antimicotic effect of thymol in concentrations of 0.1, 0.5 and 1 % on strains of Candida albicans evaluated at 48 hours of incubation, comparing them with 0.12 % chlorhexidine gluconate and nystatin. Material and methods: Thymol antifungal activity was determined according to the inhibition halo diameter and the susceptibility criteria of the Duraffoourd method, carried out according to the agar diffusion technique with a sample of 25 Petri dishes inoculated with Candida albicans. ATCC®10231, each with 3 filter paper discs embedded in 0.1 %, 0.5 % and 1 % thymol solutions, as in 0.12 % chlorhexidine gluconate and nystatin in suspension following the parameters of National Committee of Standards of Clinical Laboratories. Results: Thymol concentrations of 0.5 and 1% showed an inhibitory effect superior to the substances used as control. Conclusions: Thymol has a greater inhibitory effect than chlorhexidine and nystatin on Candida albicans cells, being shown as an alternative to the usual drugs.